Endoscopic management of lower ureteric stone after ureterosigmoidostomy - KC, HB; Chalise, PR; Bhattarai, A; Sharma, UK; Gyawali, P; Shrestha, GK; Joshi, BR (Journal of Institute of Medicine Nepal, 2010)
Ureterosigmoidostomy is one of the oldest technique for continent urinary diversion. Though less common nowadays, it is still a useful form of urinary diversion; simple to perform, offers good continence with minimal interference with life style. It still has a major role in conditions like ectopia vesicae and post-radical cystectomy for bladder carcinoma. We present a case of 33 years lady who underwent ureterosigmoidostomy at the age of 10 years for ectopia vesicae and later developed left pyonephrosis due to distal ureteric calculus. Left sided PCN was done and successful antegrade endoscopic removal of calculus relieved her symptoms. DOI: http://dx.doi.org/10.3126/joim.v32i1.4004 Journal of Institute of Medicine, April, 2010; 32:1 pp.46-49